2003
DOI: 10.1046/j.1365-2249.2003.02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Restricted genetic defects underlie human complement C6 deficiency

Abstract: SUMMARY Complement C6 homozygous deficiency (C6D) has been rarely observed in Caucasians but was reported at higher prevalence among African‐Americans. We report on the molecular basis of C6D in seven unrelated black individuals of North or Central Africa descent who live in France. These patients have presented Neisseria meningitidis infection (four cases), focal and segmental glomerulosclerosis with hyalinosis (one case), systemic lupus erythematosus (one case) or Still's disease (one case). All patients exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…While defects in the C2 and C6 genes are known to be associated to a few mutation hot spots [19,20], C7 mutations seem more heterogeneous. In agreement with the relative diversity of molecular defects observed previously carried by the C7 gene, we found three novel mutations expected to be deleterious for C7 protein production or function.…”
Section: Discussionmentioning
confidence: 99%
“…While defects in the C2 and C6 genes are known to be associated to a few mutation hot spots [19,20], C7 mutations seem more heterogeneous. In agreement with the relative diversity of molecular defects observed previously carried by the C7 gene, we found three novel mutations expected to be deleterious for C7 protein production or function.…”
Section: Discussionmentioning
confidence: 99%
“…C5 sera concentration was measured by a rabbit double‐ligand enzyme‐linked immunosorbent assay (ELISA) test (home‐made) using a polyclonal anti‐human C5 antibody (Calbiochem, Meudon, France) 6 . Results were expressed as percentages according to a pool of 100 healthy controls.…”
Section: Demographic Characteristics Of Patients and Healthy Controlmentioning
confidence: 99%
“…Complement activation plays an important role in the pathogenesis of several pathological processes, such as ischemia and reperfusion injury occurring in myocardial infarction and stroke, hyperacute graft rejection and antibody‐mediated autoimmune diseases (Nauta et al 2002). On the other hand, deficiencies of C6 result in remarkable susceptibility to meningococcal infections or development of autoimmune diseases (Dragon‐Durey et al 2003) (C6 deficiency [MIM 217050]). In addition to a cytolytic function, recent studies suggested a role of the MAC in the cell cycle and apoptosis (Rus et al 2001).…”
Section: Resultsmentioning
confidence: 99%